Customers awareness towards Usages Pattern of Mobile Banking Services - Mangla, Sheetal; Singh, Swati; Atwal, Virender (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In the contemporary digital landscape, mobile banking has fundamentally transformed the delivery of financial services by providing customers with enhanced convenience, rapidity, and accessibility. Nonetheless, the efficacious adoption and utilization of mobile banking services are predominantly contingent upon the degree of customer awareness and digital literacy. This research endeavors to assess the level of customer cognizance pertaining to mobile banking. Employing a descriptive research design, the study utilized a structured questionnaire to gather primary data from 300 participants representing both urban and rural demographics. The results reveal that, although foundational awareness of mobile banking exists at a relatively high level, a significant proportion of users lack comprehensive knowledge of the full spectrum of available functionalities. Sociodemographic factors including age, educational attainment, and income exert a substantial influence on awareness levels. Furthermore, concerns related to trust and security constitute notable impediments to broader adoption. The analysis further delineates variability in awareness across distinct mobile banking services: while functionalities such as Transaction Inquiry, Account Statements, and SMS Alerts exhibit higher recognition, critical features like UPI, Balance Inquiry, and Bill Payment remain underrecognized. To foster effective digital financial inclusion, it is imperative that users receive adequate education to fully comprehend and exploit these digital financial instruments.